Understanding art [videorecording (DVD)] : impressionism - Januszczak, Waldemar (Athena ; Distributed by Acorn Media, 2012)
Today Impressionist art is found on T-shirts and mugs, but it wasn't always popular. London Sunday Times art critic Waldemar Januszczak hosts a lively guide to these revolutionary and influential artists, visiting their studios and the rustic vistas that inspired them. It's a super introduction to Monet, Manet, Degas, Seurat, Cezanne, Pissarro, Berthe Morisot, Mary Cassat, Van Gogh, and other greats.